PSYCHOLOGICAL TRAINING OF ATHLETES AND ITS IMPORTANCE (Archive of Conferences, 2021)
This article describes how children often feel bad under the influence of psychological stimuli, and sometimes lack psychological preparation and technique as a result of thinking without thinking.